Pengaruh Tata Niaga Tembakau dan Alternatif Pengganti Tembakau Bagi Petani di Pamekasan - Syaiful Syaiful; Ria Kasanova; Alfi Hasaniyah (LP2M IAI Nazhatut Thullab Sampang, 2019)
Tobacco is one of the important commodities, the role of tobacco and the tobacco product industry in the socio-economic life of the community has a significant role in the form of excise, employment, and sources of income for farmers, laborers, or traders, even regional income. Tobacco in Madura is cultivated from generation to generation by the Madurese, compared to other plant commodities, this tobacco provides hope of considerable profits. Therefore, tobacco is always used as a superior commodity, especially in Pamekasan and Sumenep Regencies. While the poles opposing the tobacco trading system are still largely monopolized by certain parties, so farmers are not given enough space in determining quality and price. This research is intended to find a way out for farmers who are still dependent on tobacco products. This research study uses descriptive qualitative research methods. Data collection techniques carried out by observation, interviews, literature study and documentation. The results of this study are the trading system that occurs in the absolute market mechanism is still a monopoly between farmers and traders and so on, even the government that is detected also takes part in the profits, so farmers are fed up to produce tobacco again. So there must be a substitute plant that is a suitable plant to replace tobacco plants are banana trees and chilies.